Endogenous HLA-DQ8αβ programs superantigens (SEG/SEI) to silence toxicity and unleash a tumoricidal network with long-term melanoma survival - David Bradley; Peter Knopick; David Terman; Nathan Riha; Travis Alvine; Riley Larson; Cedric Badiou; Gerard Lina; John Ballantyne (Journal for ImmunoTherapy of Cancer)
Background As the most powerful T cell agonists known, superantigens (SAgs) have enormous potential for cancer immunotherapy. Their development has languished due to high incidence (60%–80%) of seroreactive neutralizing antibodies in humans and tumor necrosis factor-α (TNFα)-mediated cardiopulmonary toxicity. Such toxicity has narrowed their therapeutic index while neutralizing antibodies have nullified their therapeutic effects.Methods Female HLA-DQ8 (DQA*0301/DQB*0302) tg mice expressing the human major histocompatibility complex II (MHCII) HLA-DQ8 allele on a high proportion of PBL, spleen and lymph node cells were used. In the established tumor model, staphylococcal enterotoxin G and staphylococcal enterotoxin I (SEG/ SEI) (50 µg each) were injected on days 6 and 9 following tumor inoculation. Lymphoid, myeloid cells and tumor cell digests from tumor tissue were assayed using flow cytometry or quantitated using a cytometric bead array. Tumor density, necrotic and viable areas were quantitated using the ImageJ software.Results In a discovery-driven effort to address these problems we introduce a heretofore unrecognized binary complex comprizing SEG/SEI SAgs linked to the endogenous human MHCII HLA-DQ8 allele in humanized mice. By contrast to staphylococcal enterotoxin A (SEA) and staphylococcal enterotoxin B (SEB) deployed previously in clinical trials, SEG and SEI does not exhibit neutralizing antibodies in humans or TNFα-mediated toxicity in humanized HLA-DQ8 mice. In the latter model wherein SAg behavior is known to be ‘human-like’, SEG/SEI induced a powerful tumoricidal response and long-term survival against established melanoma in 82% of mice. Other SAgs deployed in the same model displayed toxic shock. Initially, HLA-DQ8 mediated melanoma antigen priming, after which SEG/SEI unleashed a broad CD4+ and CD8+ antitumor network marked by expansion of melanoma reactive T cells and interferon-γ (IFNy) in the tumor microenvironment (TME). SEG/SEI further initiated chemotactic recruitment of tumor reactive T cells to the TME converting the tumor from ‘cold’ to a ‘hot’. Long-term survivors displayed remarkable resistance to parental tumor rechallenge along with the appearance of tumor specific memory and tumor reactive T memory cells.Conclusions Collectively, these findings show for the first time that the SEG/SEI-(HLA-DQ8) empowers priming, expansion and recruitment of a population of tumor reactive T cells culminating in tumor specific memory and long-term survival devoid of toxicity. These properties distinguish SEG/SEI from other SAgs used previously in human tumor immunotherapy. Consolidation of these principles within the SEG/SEI-(HLA-DQ8) complex constitutes a conceptually new therapeutic weapon with compelling translational potential.